2022
DOI: 10.1177/09544070221093184
|View full text |Cite
|
Sign up to set email alerts
|

A novel on the retrofit from CNG buses to electric buses for rubber-tyred wheeled public transportation systems

Abstract: The trend toward electric buses worldwide is increasing day by day. Along with it, sectoral infrastructure elements are developing rapidly. Electric buses offer advantages in terms of operating costs and environmental emission values. Despite this, the most important disadvantage is that the purchasing costs have not yet reached the expected level compared to other internal combustion engine buses. Many country and especially city-based targets have been determined for electric solutions in rubber-tyred public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Maintenance and repair costs for electric buses may become challenging to maintain the determined performance conditions, especially after the first 5-year period. Renewing the powertrain battery at least 2 times within the stipulated period leads to a significant increase in maintenance and repair unit costs (Topal, 2023). It has been reported that the maintenance & repair process under warranty continues for the electric buses in Elazig Municipality which are referenced in this study (EKAP, 2017).…”
Section: The Financial Model For 100 % Zero Emission Concept On Istan...mentioning
confidence: 90%
See 1 more Smart Citation
“…Maintenance and repair costs for electric buses may become challenging to maintain the determined performance conditions, especially after the first 5-year period. Renewing the powertrain battery at least 2 times within the stipulated period leads to a significant increase in maintenance and repair unit costs (Topal, 2023). It has been reported that the maintenance & repair process under warranty continues for the electric buses in Elazig Municipality which are referenced in this study (EKAP, 2017).…”
Section: The Financial Model For 100 % Zero Emission Concept On Istan...mentioning
confidence: 90%
“…This is important in terms of cost and operational continuity. Additionally, the training of bus drivers and maintenance staff enhances efficiency (Topal, 2023).…”
Section: The Main Operating Costs For Bus Concepts On Modelmentioning
confidence: 99%
“…In the medium/long term, low energy (fuel) costs, incentives for reduced (or zero) emissions and renewable energy-supported charging station installation, as well as a reduction in maintenance & repair costs, and high initial purchase costs for electric vehicle concepts, are considered as a balancing factor. [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%